LINGUISTIC AND CULTURAL ADAPTATION AND VALIDATION OF THE KUJALA QUESTIONNAIRE AMONG PATIENTS WITH PAIN IN THE ANTERIOR PART OF KNEE JOINT - I. A. Kuznetsov; S. V Maikov; M. R. Salikhov; D. A. Shulepov; A. I. Avdeev (Научно-практическая ревматология)
Objective: to carry out linguistic and cultural adaptation and validation of the Kujala questionnaire that is today one of the most popular orthopedic tools used to evaluate the severity of pain in the anterior part of knee joint.Subjects and methods. In accordance with protocols on this type of investigations, the questionnaire was first translated directly and then back. Furthermore, an intermediate Russian-language version of the Kujala questionnaire was tested in 15 patients, followed by error correction and approval of its final Russian-language version. A study group included 50 patients who complained of obvious pain in the anterior part of knee joint and answered the questionnaire twice (for its test-retest reliability) every two or three days.Results and discussion. The intraclass correlation coefficient (ICC) equal to 0.948 (95% confidence interval, 0.025–0.967) indicated a high test-retest reliability of the Russian-language version of the Kujala questionnaire. Cronbach's alpha coefficient of 0.956 corresponded to a high level of internal consistency, which also suggested that the proposed version of the questionnaire had a high reliability. The criterion-related validity assessment, by calculating the Spearman correlation coefficient between the results of primary and repeated surveys using the Russian-language version of the Kujala questionnaire, as well as between the Russian- language versions of the Kujala questionnaire and the SF-36, showed their high correlation.Conclusion. The findings indicate that the Russian-language version of the Kujala questionnaire is a valid and reliable tool for subjective assessment of the severity of pain in the anterior part of knee joint.